Metal forming progress since 2000 - Jeswiet, J.; Geiger, Manfred; Engel, Ulf; Kleiner, M.; Schikorra, M.; Duflou, J.; Neugebauer, R.; Bariani, P.; Bruschi, S. (CIRP Journal of Manufacturing Science and Technology, 2008)
Considerable changes have occurred in metal forming in the last decade. A record of these changes can be found in keynote papers presented by the members of the Scientific Technical Committee-Forming, at the CIRP Annual General Meeting each year. The keynote papers are excellent references on important developments in metal forming and are used as a reference, globally. Not only is this paper a compendium of most of the keynotes presented, but from 2001 onward, it has updates on new information on five keynote subject areas. The authors of each keynote have written an update with new information that has developed since the writing of the keynote. The authors of each section are shown in order of presentation. © 2008.
LFT Import::2019-07-29 (1534)
Keywords: Metal forming